2017
DOI: 10.1080/10872981.2017.1267980
|View full text |Cite
|
Sign up to set email alerts
|

Training US health care professionals on human trafficking: where do we go from here?

Abstract: Some 21 million adults and children are labor-trafficked or sex-trafficked through force, fraud, or coercion. In recognition of the interface between trafficking victims and the healthcare setting, over the last 10 years there has been a notable increase in training of health care professionals (HCPs) on human trafficking (HT) and its health implications. Many organizations have developed curricula and offered training in various clinical settings. However, methods and content of this education on trafficking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(62 citation statements)
references
References 32 publications
1
60
0
1
Order By: Relevance
“…Unfortunately, trafficked patients are often unidentified due to lack of education available to HCPs at all levels of training and practice [6,7]. A survey of medical professionals including physicians, nurses, social workers, and physician assistants found that 63% of respondents did not have training on human trafficking identification and intervention [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, trafficked patients are often unidentified due to lack of education available to HCPs at all levels of training and practice [6,7]. A survey of medical professionals including physicians, nurses, social workers, and physician assistants found that 63% of respondents did not have training on human trafficking identification and intervention [8].…”
Section: Introductionmentioning
confidence: 99%
“…To improve victim identification and quality of care in healthcare settings, providers need to be educated about the issue of trafficking, including its clinical presentations. The topic requires an interactive format that maximizes HCP learning, hones communications skills, and focuses on patient-centered outcomes [7,9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…Such innovations can inform emerging practice in the UK. All these interventions require careful design, application and evaluation (22).…”
Section: Q2: What Should Be the Scope And Role Of Hcps And Services?mentioning
confidence: 99%
“…Currently available options for provider instruction on HT include multiday seminars, brief online courses, massive open online courses, guidelines, and published summaries for self‐directed learning . To our knowledge, there are no published “train‐the‐trainer” interventions focusing on EPs or providing instructional methods directed at teaching learners in the clinical environment.…”
Section: Introductionmentioning
confidence: 99%